P73 Is intraoperative frozen section needed to assess myometrial infiltration in endometrial cancer (EC)? A multicentre study in oncological network of piemonte and valle d'aosta. (1st November 2019) - Baima Poma, C; Cotrino, I; Ribotta, M; Fuso, L; Ferrero, A; Mariani, LL; Macchi, C; Laudani, ME; Lerda, D; Potenza, E; Zola, P
Abstract : Introduction/Background: In developed countries, endometrial cancer is the fourth most common cancer in women. ESGO guidelines propose appropriate strategies based on risk factors. Lymphadenectomy is a staging procedure and even if it does not seem to have a therapeutic role, it is crucial for tailoring adjuvant therapy. The aim of the study is to verify the reliability of expert transvaginal sonographer (TVS) and frozen section (FS) to assess myometrial infiltration (<50% vs ≥50%) to limit systematic lymphadenectomy where not indicated. Methodology: To verify the accuracy of expert TVS and intraoperative frozen section to evaluate myometrial infiltration, 364 consecutive patients affected by EC were prospectively followed in 3 centres of the Oncological Network of Piemonte and Valle d'Aosta from 01/2016 to 10/2018. Definitive pathological report sensitivity, specificity, PPV, NPV, LR + LR- of TVUS and FS are obtained. The results were evaluated overall and by centre. Results: TVUS by expert ultra-sonographer has obtained a diagnostic accuracy with sensitivity 76% specificity 73% PPV 66% NPP 82%. The variability observed between hospitals: centre A sensitivity 76% specificity 86% PPV 85% NPP 82%; centre B sensitivity 60% specificity 75% PPV 59% NPP 76%; centre C sensitivity 95% specificity 58% PPV 58% NPP 95%. The overall FS examination has the following values: sensitivity 86% specificity 97% PPV 95% NPP 92%. Stratifying by centres: A sensitivity 91% specificity 96% PPV 95% NPP 93%; B sensitivity 87% specificity 97% PPV 93% NPP 95%; C sensitivity 85% specificity 100% PPV 100% NPP 91%. Patients who add FS to TVUS had a reclassification improvement of 7.5%. Conclusion: FS remains the most reliable method in the 'real world' to assess myometrial infiltration and to direct the staging procedures in endometrial cancer. The variability of FS among centres belonging to an oncological network is lower than what observed for TVUS. Disclosure: Prof. Paolo Zola has received grants from Astrazeneca, Roche, Pharmamar and Tesaro.